Modeling Microwave Oven Sterilization of Palm Fruit using Response Surface Methodology (RSM) - Lavlinesia; Arzita; Dewi Fortuna; Diana Pebriani Daulay; Eli Sovia (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2025)
The conventional steam-based sterilization of crude palm oil (CPO) in Indonesia is known to be energy- and water-intensive, as well as time-consuming. This necessitates more efficient and sustainable alternatives, such as microwave oven heating. While microwave applications in CPO sterilization have been explored as a more efficient and sustainable alternative, existing studies often lack comprehensive optimization and a systematic investigation of key process parameters. This study aimed to optimize fresh fruit bunch (FFB) sterilization using a microwave oven to identify optimal operating parameters for maximizing oil extraction yield and minimizing Free Fatty Acid (FFA) content. The Central Composite Design (CCD) within Response Surface Methodology (RSM) was employed as a statistical technique to model the process and ensure the validity of the results. Three independent variables were investigated: sterilization time (6–20 min), fruit mass (396–1104 g), and fruit maturity level (ripe and over-ripe), resulting in twenty-six experimental combinations. Optimal conditions for maximum yield and lowest FFA were determined at 6 min sterilization time and 550 g fruit mass for both maturity levels. Conversely, suboptimal conditions at 11.5 min and 150 g fruit mass for both maturity levels resulted in the lowest yield and highest FFA. This research provides crucial insights for developing an optimized microwave sterilization technique, enhancing palm oil processing efficiency and product quality. The findings underscore the potential for a scalable, low-energy sterilization method that could significantly reduce the environmental footprint of CPO production, instilling optimism about the positive impact of this research.